Female Labor Force Participation in Pakistan: A Case of Punjab - Shaheen, Safana; Sial, Maqbool Hussain; ., Masood Sarwar Awan (Journal of Social and Development Sciences, 2011)
The present study is an effort to investigate the patterns of female labor force participation in case of Pakistan. In particular, the study analyzed the determinants of female labor force participation decision. The study utilized Multiple Indicator Cluster Survey 2007-08 data of Punjab. Education is used as a direct human capital variable while; age is a proxy of human capital. The variables used in the analysis are female labour force participation, age, age square, marital status, area, female monthly income, family monthly income, family size, household head education, different classes of female education and employment status. To remove the selectivity bias, the study used Heckman’s (1979) two step procedure. Results of Logit model depicts that household head education, primary, middle, matric & mudrassa education level negatively related with the decision of female labor force participation while, decision towards participation is strong if female belonged to urban area, if she is married, if she has higher education, and if she has large family size. By using ordinary Least Square Method we estimated the earning function. Coefficient of age shows a substantial increase in the wages with each additional year spent. The sign of age square is negative which is according to our expectation and implying the concavity of earning function. Moreover, as the level of education increase the returns to each year of education also increases. In different occupational status females earns more if they are employee, employer or self employed than labourer (a reference category); while female earns less if they belonged to agricultural sector or other sectors than labourer. Married females earn more than others. The respondents’ belonged to urban areas earn more than rural respondents. Moreover, household head education and family size are positively significantly related with female earnings.